Development and evaluation of the psychometric properties of a new measure of athlete insomnia: Insomnia in Response to Sports-related Stress Test questionnaire - Nedelec, M.; Chauvineau, M.; Martinent, G. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Impaired sleep is particularly frequent among elite athletes which has been linked to various negative consequences, including lower athletic performance and general health [1]. Several studies have examined potential acute and chronic factors placed on elite athletes resulting in compromised sleep, e.g. training and competition [1]. Candidate risk factors for compromised sleep in elite athletes also include many factors commonly considered to influence sleep in non-athletic individuals and particularly psychological stress and anxiety [2]. The aim of the present study was to develop and validate the Insomnia in Response to Sports-related Stress Test (IRSST) questionnaire, a new specific instrument with the goal of sensitively measuring vulnerability to sport-specific stressful situations among elite athletes.